2014
DOI: 10.1042/cs20130450
|View full text |Cite
|
Sign up to set email alerts
|

Protective axis of the renin–angiotensin system in the brain

Abstract: The RAS (renin-angiotensin system) is composed of two arms: the pressor arm containing AngII (angiotensin II)/ACE (angiotensin-converting enzyme)/AT1Rs (AngII type 1 receptors), and the depressor arm represented by Ang-(1-7) [angiotensin-(1-7)]/ACE2/Mas receptors. All of the components of the RAS are present in the brain. Within the brain, Ang-(1-7) contributes to the regulation of BP (blood pressure) by acting at regions that control cardiovascular function such that, when Ang-(1-7) is injected into the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 89 publications
1
47
1
1
Order By: Relevance
“…1,2 It was surprising to find that Ang-(1–7) stimulation did not elicit Akt activation (present results). Despite that, constitutive Akt activation was present in MasR-transfected cells, suggesting that MasR activation is coupled to Akt activation despite the fact that Ang-(1–7) was absent.…”
Section: Discussioncontrasting
confidence: 50%
“…1,2 It was surprising to find that Ang-(1–7) stimulation did not elicit Akt activation (present results). Despite that, constitutive Akt activation was present in MasR-transfected cells, suggesting that MasR activation is coupled to Akt activation despite the fact that Ang-(1–7) was absent.…”
Section: Discussioncontrasting
confidence: 50%
“…11 Immunostaining for Ang-(1–7) has been observed in the areas of the brain, including the supra-optic and paraventricular nucleus (PVN) of the hypothalamus, neurons from the hypothalamus, and brainstem. 8 Furthermore, the level of Ang-(1–7) was detected from the hippocampus using high-performance liquid chromatography assay and increased during the acute and silent phases of pilocarpine-induced epilepsy. 12 Pereira et al 13 show that Ang-(1–7) is the main metabolite of Ang I in rat hippocampi.…”
Section: Discussionmentioning
confidence: 99%
“…8 ACE2 is widely expressed in brain areas involved in both the central regulation of blood pressure and cardiovascular function and disease, and the ACE2 level appears to be strongly regulated by other components of RAS. 11 Immunostaining for Ang-(1–7) has been observed in the areas of the brain, including the supra-optic and paraventricular nucleus (PVN) of the hypothalamus, neurons from the hypothalamus, and brainstem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Previous peripheral experiments have shown that the actions of Ang-(1-7) mainly oppose the detrimental cardiovascular effects of angiotensin II, such as hypertension and cardiac hypertrophy. 4,5 Ang-(1-7) is widely distributed throughout the brain, including the PVN.…”
Section: Introductionmentioning
confidence: 99%